Genesis of the Longmendian Ag–Pb–Zn Deposit in Henan (Central China): Constraints from Fluid Inclusions and H–C–O–S–Pb Isotopes. (13th July 2020) - Chen, Xinglin; Shao, Yongjun; Lai, Chunkit; Wang, Cheng
Abstract : The Longmendian Ag–Pb–Zn deposit is located in the southern margin of the North China Craton, and the mineralization occurs mainly in quartz veins, altered gneissic wallrocks, and minor fault breccias in the Taihua Group. Based on vein crosscutting relations, mineral assemblages, and paragenesis, the mineralization can be divided into three stages: (1) quartz–pyrite, (2) quartz–polymetallic sulfides, and (3) quartz–carbonate–polymetallic sulfides. Wallrock alteration can be divided into three zones, i.e., chlorite–sericite, quartz–carbonate–sericite, and silicate. Fluid inclusions in all Stage 1 to 3 quartz are dominated by vapor-liquid two-phase aqueous type (W-type). Petrographic and microthermometric analyses of the fluid inclusions indicate that the homogenization temperatures of Stages 1, 2, and 3 are 198–332°C, 132–260°C, and 97–166°C, with salinities of 4.0–13.3, 1.1–13.1, and 1.9–7.6 wt% NaCleqv, respectively. The vapor comprises primarily H2 O, with some CO2, H2, CO, N2, and CH4 . The liquid phase contains Ca 2+, Na +, K +, SO4 2−, Cl −, and F − . The sulfides have δ 34 S = – 1.42 to +2.35‰ and 208 Pb / 204 Pb = 37.771 to 38.795, 207 Pb / 204 Pb = 15.388 to 15.686, and 206 Pb / 204 Pb = 17.660 to 18.101. The H–C–O–S–Pb isotope compositions indicate that the ore-forming materials may have been derived from the Taihua Group and the granitic magma. The fluid boiling and cooling and mixing with meteoric water may have been critical for the Ag–Pb–Zn ore precipitation. Geological and geochemical characteristics of the Longmendian deposit indicate that the deposit is best classified as medium- to low-temperature intermediate-sulfidation (LS/IS) epithermal-type, related to Cretaceous crustal-extension-related granitic magmatism.